ADHERENCE LEVEL AND BLOOD SUGAR CONTROL OF TYPE 2 DIABETES MELLITUS PATIENTS WHO GETS COUNSELING AND SHORT MESSAGES SERVICE AS REMINDER AND MOTIVATION - Adikusuma, Wirawan; Qiyaam, Nurul (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Examines the effects of counseling and short messages service (SMS) as a reminder and motivation toward medication adherence improvement and controlled HbA1c levels of type 2 diabetes mellitus (T2DM) patients. Methods: This study used a quasi-experimental method with prospective data retrieval. The subjects of this study were 40 patients with outpatient T2DM in internal disease polyclinic in West Nusa Tenggara Hospital, Indonesia. Patients who fulfilled the inclusion criteria were divided into two groups: The control group (n=20) receiving only the drug care service and the treatment group (n=20) receiving counseling and SMS reminder and motivation from the pharmacist. Data collecting was conducted using the pill count method, and HbA1c levels were taken from the medical record. Results: The results showed that counseling and SMS as reminder and motivation by a pharmacist can improve treatment adherence significantly (p<0.05) by 11.33 ± 8.47 and can decrease HbA1c level significantly (p<0.05) of 1.32 ± 0.72 in the intervention group. There was a positive correlation between T2DM patient treatment adherence to HbA1c levels (r=0.254, p=0.023). Conclusion: The provision of counseling and SMS as a reminder and motivation by the pharmacist can have a positive effect toward medication adherence and control of HbA1c in T2DM patients.